Laboratory estimation of the hybrid zone structure of the adhesive system based on the ormoker at filling class I cavity - A. V. Mitronin; M. N. Kuvaeva; S. N. Vovk (Эндодонтия Today)
Relevance. Many dentists in their clinical practice use a two-time adhesion protocol, which does not always follow the manufacturer's instructions, believing that they achieve improved adhesion of the filling material to the tooth tissues. To solve the problems associated with increasing the compressive strength of adhesive materials, a single-bottle adhesive system was developed based on the technology of organically modified ceramics (Admira Bond, VOCO GmbH Germany). Despite the fact that the Admira Bond adhesive system is already used in practical dentistry, its adhesion to hard tooth tissues and the characteristics of the hybrid zone when used according to the manufacturer’s instructions and the protocol providing for double application of the adhesive for restoration of the tooth have not been sufficiently studied.Aim. To study the structure of the hybrid zone using a scanning electron microscope using an Admira Bond adhesive system based on Ormoker.Materials and methods. Using a remote survey on the frequency of use of various adhesive protocols, identify the most commonly used and compare the selected protocols on samples of longitudinal sections of teeth using a Tescan Mira LMU scanning electron microscope.Results. I n a s ample p repared b y t he a dhesive p rotocol o f d ouble a pplication o f a dhesive, t he t hickness o f t he hybridization zone is 1 μm. The distribution of adhesive over the dentin surface is uneven. The adhesive system was infiltrated into the filling material.Conclusions. When using the protocol according to the manufacturer's instructions, a higher quality of hybridization, uniformity of structure and uniform distribution of the Admira Bond adhesive system based on Ormoker on the dentin surface are noted than when using the protocol of double application. This confirms that deviation from the manufacturer's recommended protocol for using Admira Bond adhesive system based on Ormoker, reliably leads to a deterioration in the adhesion strength of the filling material to the dentin of the tooth.